Analysis of extension gap among improved bread wheat producer's farmers found at Arsi Robe District of Arsi Zone, Oromia Regional State, Ethiopia - Sintayehu Abebe (Open Journal of Plant Science - Peertechz Publications, 2021)
This study reports the analysis of agricultural extension gap among four improved bread wheat varieties at Arsi Robe district, Arsi Zone, along with their management practices under farmers 'condition to enhance farmers' knowledge and skill on bread wheat production.  Four improved bread wheat varieties were used to demonstrate namely Honkolo,DEKA,Hidase(check) and Lemu. Honkolo variety had a 43.8% yield advantage over the standard check (Hidase), DEKA had a 16.4% yield advantage over the standard check (Hidase), and the variety Lemu had a negative -25.8% yield loss or below the standard check (Hidase) and it conclude that both Honkolo and DEKA varieties are the first and second option for the farmers whereas the variety Lemu is not recommended due to low productivity in the study area and others areas having similar agro ecologies. The result of agricultural extension gap analysis showed that Honkolo variety had a -2.7q/ha yield increment or in other words Honkolo variety had achieved 104.3% of the potential at research field and had a 4.3% yield advantage than the research field. According to the result DEKA variety had a 2.8q/ha yield gap or in other words DEKA variety had achieved 95% of the potential and the remaining 5% lack due to extension gap. Again the result Hidase variety had a 24.3q/ha yield reduction or in other words Hidase variety had achieved 65.3% of the potential and had a 34.7% yield penalty than the research field. Again the result Lemu variety had a 31.1q/ha yield reduction or in other words Lemu variety had achieved 52.2% of the potential and had a 47.8% yield penalty than the research field. Therefore, the lower the percentage of agricultural extension gap the higher will be the option for the production. The agricultural extension gap analysis indicate that there is no extension gap in terms of Honkolo variety where as there is a bit extension gap (5%) among DEKA variety producer farmers  and a wide extension gap among Hidase and lemu varieties producer farmers. And in their average yield gap and yield performance between demonstration conducted at farmers field and the potential of the varieties at research field, having -2.7 q/ha, 2.8q/ha, 24.3q/ha and 31.1q/ha for Honkolo, DEKA, Hidase and Lemu respectively. This indicates that the varieties Honkolo and DEKA are the first and second option of varieties for farmers respectively and both are feasible if produced in the study areas and other areas having similar agro ecologies. Based on the rules of decision making and extension gap on the bread wheat varieties producers the two varieties (Honkolo and DEKA) met the requirements for recommendation.Therefore,the authors recommend Honkolo and DAKA varieties for Arsi Robe district and other areas with similar agro-ecological conditions in the South eastern districts.